EXPLORING THE SYNERGY BETWEEN GOVERNMENT AND BUSINESS ENTITIES IN THE FIGHT AGAINST SUBSTANCE ABUSE IN EAST LONDON. A 2018-2021 STUDY - Samkelo Bala; Simon M. Kang’ethe (Social Work/Maatskaplike Werk, 2022)
South Africa’s public sector is resource deficient and that justifies the need for the government and business entities to fight synergistically against substance abuse. This study adopted a qualitative approach to explore the working synergy between government and business entities in the fight against substance abuse. The research population for this study was comprised of participants from business entities and government and non-government organisations based in East London in the Eastern Cape province. One-on-one interviews and focus group discussions were conducted to gather information from the purposively selected participants. The findings identified intermittent contributions from business entities that could be utilised in the fight against substance abuse, as well as a weak policy nexus with national policies, weak campaign synergy between government and business entities, and poor mobilisation of business entities by the government. This study encourages South African business entities to include addressing substance abuse in their corporate social investment activities. Resource mobilisation is one of the important roles in social work practice and social workers need to coordinate and facilitate the synergy between government and business entities in the fight against substance abuse.